2015
DOI: 10.1093/ehjci/jev312
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of cadmium-zinc-telluride-based myocardial perfusion SPECT: impact of attenuation correction using a co-registered external computed tomography

Abstract: Attenuation correction with a co-registered external CT is feasible using CZT cameras and improves diagnostic accuracy mostly by improving specificity over uncorrected images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…The authors reported that with visual analysis the sensitivity/specificity of CZT SPECT was 87%/67% and that with semi-automated analysis the sensitivity/ specificity was 74%/67%. 25 Overall, these studies reported high sensitivities and reasonable specificities ( Figure 1); [23][24][25] however, the number of patients in each study was limited.…”
Section: Role For Ct Attenuation Correctionmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors reported that with visual analysis the sensitivity/specificity of CZT SPECT was 87%/67% and that with semi-automated analysis the sensitivity/ specificity was 74%/67%. 25 Overall, these studies reported high sensitivities and reasonable specificities ( Figure 1); [23][24][25] however, the number of patients in each study was limited.…”
Section: Role For Ct Attenuation Correctionmentioning
confidence: 90%
“…Interestingly, the authors found significantly improved diagnostic accuracy in the RCA territory (P = 0.002) but not in the LAD (P = 0.35) or LCx (P = 0.08) territories. 23 Esteves et al investigated a subset of 55 patients that underwent coronary angiography within 2 months of CZT SPECT. In their primary analysis, there was a non-significant difference in specificity for obstructive CAD between CTAC and NAC (75% versus 44%; P = 0.15).…”
Section: Role For Ct Attenuation Correctionmentioning
confidence: 99%
“…CT attenuation would add additional cost to an already high purchase price. It could be done on a close-by free standing CT, 20 but this is not widely practiced and logistically difficult.…”
Section: Motion Detection and Attenuation Correctionmentioning
confidence: 99%
“…The degree of attenuation artifacts in CZT images is markedly higher than in conventional NaI images (Figure 1). AC using supine-prone acquisition or CTAC is a possible solution [43,44]. Although the majority of dedicated CZT gamma cameras do not include an integrated CT scanner, CTAC can be conducted using an external-CT-derived attenuation map and CTAC software.…”
Section: Ctac For Myocardial Spect Using Solid-state Gamma Camerasmentioning
confidence: 99%